KEKUATAN MENGIKAT MEMORANDUM OF UNDERSTANDING (MOU) - Ari Mahendra, Ngakan Agung; Keneng, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2013)
The focus of the study in this writing is related to the binding power of Memorandum of Understanding. This writing is based on reserach of Normative Law using library data. In discussing the problem, the research applied fact and concept of law approaches. The library data as law material were processed and analyzed descriptively. The conclusion of the research shows that seen from law jpoiint of view Memorandum Of Understanding basically has a binding power.
Keywords: Binding Power, Memorandum of Understanding